(untitled) (diségno, 2024)
Albeit with discontinuity, the history of representation is punctuated by imaginative impulses apparently lacking operational results, and for this reason dismissed as caprices or at most as divertissements, but which conversely, if taken up and developed, could have opened up new horizons. [read more]